Lower back pain in golfers: a review of the literature - McHardy, Andrew (Elsevier, 2005)
OBJECTIVE: To review the epidemiological literature on low back pain in golfers and to review the golf swing and relate the literature on the mechanics of the swing to the lower back. METHODS: A computer search was conducted of Index Medicus (1966 to 2004), MANTIS (1880 to present) and CINAHL (1982 to 2004) for literature on the following key words: low back, golf, injury. A manual search for relevant references in review papers on the subject was also conducted. The results were collated and literature fitting the criteria were collected and evaluated for suitability. RESULTS: The lower back is a common site of golf-related injury and has resulted in much research being conducted on the forces produced by the ‘modern’ swing in the low back. An analysis of the ‘modern’ swing when compared to the ‘classic’ golf swing, demonstrates lower rotational forces on the low back in the ‘classic’ swing. However, no studies exist to compare the different types of swing. CONCLUSION: The back is an area of the body that undergoes significant movement and muscular activity during the golf swing. It is likely that the significant activity and repetitive nature of the swing are associated with the high rate of injury in golfers. Modification of the golf swing has been hypothesized to reduce the incidence of low back injury in golf. Further research needs to be conducted on the various golf swings to evaluate if different swings change low back injury rates in golfers.